Elucidating the role of chalcogenide-based interface passivators in enhancing the stability of perovskite solar cells - Sadhu, Anupam (2023)
Chalcogenide-based Lewis bases are widely used in perovskite solar cells (PSCs) due to their effectiveness in passivating Pb2+ and Pb0-related defects. However, the underlying principles governing their defect passivation and the relative efficacy of different chalcogen elements remain poorly understood. This study evaluates the effectiveness of oxygen, sulfur, and selenium-based interface passivator molecules in enhancing the stability and power conversion efficiency (PCE) of perovskite solar cell devices. The hard and soft acid and base (HSAB) principle has been utilized here to gain insights into the defect passivation behavior of chalcogenide-based molecules. The photoluminescence, ideality factor, and trap density measurements reveal that the sulfide and selenide-passivated devices exhibit superior defect passivation compared to the oxide-passivated control device. In terms of stability, the average T75 lifetime (time at which 75% of the initial PCE is retained) of the oxide, sulfide, and selenide passivated samples is 6%, 30%, and 50% higher compared to their un-passivated counterparts. This enhanced stability with the sulfide and selenide-based passivators can be attributed to their soft Lewis base nature, which resulted in stronger interaction with the Pb-related defects, as evidenced by the density-functional theory calculations and X-Ray photoelectron spectroscopy study.